A comparative evaluation of hyperbaric levobupivacaine versus hyperbaric ropivacaine in parturients for elective caesarean section under spinal anaesthesia: a randomized clinical study - Koyu, Sophia; Singh, Langpoklakpam Chaoba; Devi, Mayanglambam Sushmita; Dodamani, Abid K.; Ningombam, Gracy Chanu; Thongam, Richardson (International Journal of Research in Medical Sciences, 2025)
Background: Spinal anaesthesia is the most preferred and widely used anaesthetic technique for elective lower-segment caesarean section, which offers less exposure to the potentially depressant drugs of general anaesthesia and allows early bonding between the mother and newborn as the mother is awake throughout the procedure. Levobupivacaine and Ropivacaine, are the two new long-acting amino amide local anesthetics available for clinical use. This study aimed to clinical efficacy, safety and haemodynamic changes of spinal anaesthesia with 0.5% hyperbaric Levobupivacaine versus 0.5% hyperbaric Ropivacaine. Methods: The study groups were divided into two, named group L and group R. The total sample size was 132 (66 patients in each group). Patients in Group L received 2.4 ml of 0.5% hyperbaric Levobupivacaine and Patients in Group R received 2.4 ml of 0.5% hyperbaric Ropivacaine. Results: Group R showed a quicker onset of sensory block and a faster 2-segment regression. On the other hand, Group L displayed a shorter duration of motor block. Both drugs showed promise for use in lower segment caesarean section with no significant side effects. The sensory and motor characteristics of both drugs are similar. Conclusions: The intrathecal hyperbaric Ropivacaine showed a faster onset of sensory block, while hyperbaric Levobupivacaine led to earlier motor block regression in elective lower segment caesarean section.